Business Ethics in a Transition Economy: Will the Next Russian Generation be any Better? - Jaffe, Eugene D. (Journal of business ethics, 2005)
This study investigated students’ perceptions of ethical organizational climates, attitudes towards ethical issues, and the perceived relationship between ethical behavior and success in business organizations. Comparisons were made between the attitudes of these future managers with previously published studies of Russian managers’ attitudes. A survey of 100 business students in three Moscow universities showed that their attitudes toward ethical behavior were more negative than those of Russian managers. No significant differences were found in the perceptions or attitudes of students who had attended an ethics course and those that did not. The implications for both managers and researchers were reported.